Nuovi innesti per "L’innesto" - Ivan Pupo (Il castello di Elsinore, 2018)
Ivan Pupo reviews the edition of Pirandello’s L’innesto edited by Roberto Gigliucci. The very stimulating reading of Gigliucci focuses on the presence of Darwinian suggestions and on the elements of sacred parody in the Pirandellian pièce. The philological work is interesting and innovative: Gigliucci chooses to publish a text different from the vulgate.